An Uncommon Complication with a Supraglottic Airway: The King LT. Issue 4 (15th February 2016) - Brown, Sara; Cherian, Verghese T.; Greco, Katherine; Mets, Elbert; Budde, Arne
Abstract : General anesthesia was administered in an 18-year-old man for removal of hardware from his right knee using a King Laryngeal Tube supraglottic airway. An hour after extubation, he reported inability to swallow with no respiratory distress. Examination showed an edematous uvula, which took 3 days to subside with anti-inflammatory medication. During the positioning of the King Laryngeal Tube, it was pulled back to ensure adequate ventilation. The inflated cuff could have dragged the uvula and folded it on itself, leading to venous congestion and edema.